Actitudes frente a la diversidad sexual de los estudiantes de Psicopedagogía de la Universidad Nacional de Chimborazo - Adriano Caiza, Wendy Monserrate (2021)
The present research had the general objective of analyzing the attitudes towards sexual diversity of the students of the psychopedagogy career of the National University of Chimborazo. Sexual diversity even in our times continues to be a subject of much controversy, but little by little changes are being seen in the attitudes of students and other people since sexual diversity is already a fact to which we have to adapt and familiarize, and even more so, the variety and types of diversity that exist throughout the world. Methodologically, this research work had a mixed approach and the design of the non-experimental research, the type of research was descriptive, basic for its objectives, field for the place; and the type of study was cross-sectional. The sample was non-probabilistic and intentional, settling in 83 students in the fourth, fifth and sixth semesters of the Psychopedagogy career. The instruments used for data collection was an ADHOC survey as a topic attitudes towards sexual diversity, according to the results obtained it is concluded that the majority of students have an optimal attitude towards a person who belongs to the LGBTI community and they put aside the retrograde attitudes that were previously had towards such people.